Spectral characteristics of high-latitude raw 40 MHz cosmic noise signals - C. M. Hall (Nonlinear Processes in Geophysics, 2016)
Cosmic noise at 40 MHz is measured at Ny-Ålesund (79° N, 12° E) using a relative ionospheric opacity meter ("riometer"). A riometer is normally used to determine the degree to which cosmic noise is absorbed by the intervening ionosphere, giving an indication of ionisation of the atmosphere at altitudes lower than generally monitored by other instruments. The usual course is to determine a "quiet-day" variation, this representing the galactic noise signal itself in the absence of absorption; the current signal is then subtracted from this to arrive at absorption expressed in decibels (dB). By a variety of means and assumptions, it is thereafter possible to estimate electron density profiles in the very lowest reaches of the ionosphere. Here however, the entire signal, i.e. including the cosmic noise itself, will be examined and spectral characteristics identified. It will be seen that distinct spectral subranges are evident which can, in turn, be identified with non-Gaussian processes characterised by generalised Hurst exponents, α . Considering all periods greater than 1 h, α ≈ 24, an indication of fractional Brownian motion, whereas for periods greater than 1 day α ≈ 0.9 – approximately pink noise and just in the domain of fractional Gaussian noise. The results are compared with other physical processes, suggesting that absorption of cosmic noise is characterised by a generalised Hurst exponent ≈ 1.24 and thus non-persistent fractional Brownian motion, whereas generation of cosmic noise is characterised by a generalised Hurst exponent ≈ 1. The technique unfortunately did not result in clear physical understanding of the ionospheric phenomena, and thus, in this respect, the application was not successful; the analysis could, however, be used as a tool for instrument validation.